Research Progress on Graphene Oxide (GO)/Chitosan (CS) Multifunctional Nanocomposites for Drug Delivery - Yanqiu Hu; Lei Ma; Qi Shi; Jinghang Li; Yuguang Lv; Chaoyu Song (Inorganics)
With the unprecedented progress of biomedical nanotechnology in the past few decades, traditional drug delivery systems (DDSs) have been incorporated into intelligent DDSs with stimulus responsive characteristics. Graphene oxide (GO) and Chitosan (CS) have excellent physical, chemical, mechanical, and optical properties, and their synergistic effects have attracted widespread attention in the biomedical field. In this review, we focus on the physicochemical characteristics of GO, CS, and GO/CS composites, as well as the research progress of DDS types based on GO/CS.